A Combined Location-Privacy Protective Transportable Representation - Thangamalar, C; Pradhap, C (International Journal of Computer Sciences and Engineering, 2025)
Location-aware smart phones support different location-based administrations (LBSs): customers question the LBS server and learn on the fly about their surroundings. However, such inquiries give away private information, enabling the LBS to distinguish and track users. We address this issue by proposing the first, to the best of our knowledge, user-communitarian insurance safeguarding approach on the other hand LBSs. Our solution, MobiCrowd, is basic to implement, it does not require evolving the LBS server architecture, and it does not expect third party privacy-insurance servers; still, MobiCrowd significantly improves customer location-privacy. The pickup stems from the joint effort of MobiCrowd-ready versatile devices: they keep their content information in a buffer, until it expires, and they pass it to other customers seeking such information. Essentially, the LBS does not need to be contacted unless all the communitarian peers in the vicinity need the looked for information. Hence, the customer can refund covered up from the server, unless it absolutely needs to expose herself through a query. Our results show that MobiCrowd hides a high part of location-based queries, along these lines significantly enhancing customer location-privacy. To study the impacts of different parameters, such as the joint effort level and contact rate between versatile users, we create a scourge model. Our simulations with genuine versatility datasets corroborate our model-based findings. Finally, our execution of MobiCrowd on Nokia platforms indicates that it is lightweight and the joint effort fetched is negligible.